Evaluation of solar thermal and photovoltaic systems in three milk processing plants in the Northern Huetar Region, Costa Rica - Guzmán-Hernández, Tomás J. (2020)
Fossil fuels, which currently contribute close to 85% of the primary energy consumed, will continue to be the main source to cover the energy demand of the coming years. Given this perspective, and within a framework of global climate change, renewable energy should take a greater role as sources of clean energy. Costa Rica, like most developed countries, is highly dependent on fossil fuels, mainly oil. However, unlike other areas of the planet, the potential solar energy in this country is quantified as 10 000 MW, enough energy for use in different production systems. Therefore, this work has evaluated a new application of solar thermal collector technologies and photovoltaic panels in the agricultural sector, as it is one of the most important sectors in terms of emission of greenhouse gases, which aggravates the problem of climate change. Five solar thermal and photovoltaic systems (hybrid thermosiphons, hybrid forced and PV) were designed and built in two dairies and two milk-processing plants in the Huetar Norte region of Costa Rica  in 2015. In all of them, computerized data logging systems were located and variables were measured; measurements of three years were evaluated, namely: time in hours, days, months; inlet and outlet temperatures; kWh; carbon equivalence, and economic savings. The results showed that energy consumption was reduced and, notably, greenhouse gas and carbon equivalent emissions, thanks to the use of solar energy. In addition, environmental pollution was lessened by the reduction of smoke due to the burning of firewood; greater independence was generated at the energetic level in associations and companies, and their products could eventually be certified as organic products.